The influence of internet finance on the profitability of commercial banks in China / Jiahui Chen …[et al.] - Chen, Jiahui; Yahya, Mohamed Hisham; Ali, Muhammad Hafiz; Qamas, Mohd Akbal (Universiti Teknologi MARA, 2022)
The emergence of internet finance is dominating the commercial bank’s market and replacing some of its roles. Hence, this study intends to investigate the impact of internet finance services; 1) third-party internet payment) and 2) peer-to-peer (P2P) online lending, towards commercial banks in China. Therefore, this study aims to analyse the impact of (1) third-party payment and (2) P2P online lending on the profitability of commercial banks, and (3) to investigate the different impact of internet finance on profitability of commercial banks by types. This study uses EViews to regress the annual data of 16 commercial banks in China from 2008 to 2018. The dependent variable is Return On Assets (ROA) of commercial banks. The independent variables are third-party internet payment and P2P online lending. In order to preserve the fairness in findings, total bank assets, non-performing loan ratio and gross domestic product growth were set as the control variables. The findings highlight that third party internet payment has a significant negative effect, while P2P online lending exhibits a positive effect on the banks’ profit. Moreover, the effect varies with different types of banks. Joint-stock commercial banks are more affected by third-party payment, and obtain relatively smaller profit from P2P online lending in comparison with state-owned banks. This study solidifies that internet finance does affect commercial bank’s profit and commercial banks should mutually cooperate with Internet finance platforms to capitalise on its development.